Enhanced spin–orbit torque efficiency in Pt/Co/Ho heterostructures via inserting Ho layer - Jin, Tianli (2020)
Spin–orbit torque (SOT) is a promising approach to manipulate the magnetization for high-performance spintronic applications. In conventional SOT heterostructures with heavy metal (HM)/ferromagnet layers, the SOT efficiency is determined by the charge-to-spin conversion, characterized by the spin Hall angle θSH of the HM layer. Researchers have investigated various HMs with different θSH to enhance the SOT efficiency while it is still limited because of the HM’s intrinsic properties. In this study, we employ a rare-earth holmium (Ho) layer on top of a ferromagnetic Co layer (Pt/Co/Ho) to enhance the SOT efficiency. An increased damping-like SOT efficiency up to 200% is achieved at an optimized thickness of 2-nm Ho, corresponding to a lower switching current density, which is 60% less compared to the sample without a Ho layer. The damping-like torque efficiency per current density is estimated at around 0.256 for Pt/Co/Ho heterostructures. Our results, herein, demonstrate that inserting a rare-earth metal affords an additional spin current and/or improves the spin transparency to enhance the SOT efficiency, providing a route for energy-efficient spintronic devices.